(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
This paper analyses the response of the Municipality of Barcelona to the Syrian refugee crisis in Europe as an alternative solution that challenges the national government’s restrictive approach. This response introduces the Ciutat Refugi Plan with a city-to-city network at the municipal level that involves other European cities in creating safe routes for refugees at the local government level. In line with multi-level governance theory, I argue that central governments’ inaction has pressured local governments to take action during the Syrian refugee influx. Relying on the influence of local government networks, the Municipality of Barcelona uses discourse as a tool of action in opening discursive spaces for humanitarian political responses to the refugee crisis. Using critical discourse analysis, I test this argument by examining in-depth interviews, speeches of people in power that have appeared in news articles, and statements on official websites.